PENANAMAN MANGROVE (Rhizophora apiculata) UNTUK PENCEGAHAN ABRASI DI PANTAI ANGSANA, TANAH BUMBU - Prastiyo, Riko; Putri, Humaira; Hutapea, Sarah Ryka Ully; S, Daniel Fredianto; Setiawati, Mariani; Pratama, Rangga Fadhil; Zahrah, Munasyifa Aulia; Prayoga, Muhammad Shafa; Ramadhan, Khalista; Kristin, Meli; Nazmi, Muhammad Fiqrian; Rizfa, Mila Safitri (Universitas Mataram, 2025)
The mangrove planting activity in Angsana Village, Angsana District, Tanah Bumbu Regency was carried out to prevent coastal abrasion and preserve the coastal ecosystem. This program was implemented as part of a community service initiative by the Universitas Lambung Mangkurat student community service program (KKN), in collaboration with the village government, local agencies, private companies, and local residents, through the planting of 300 Rhizophora apiculata seedlings in the estuarine coastal area. The activity method included direct observation at the planting site to identify the physical condition of the coast and assess land suitability for mangrove growth. The program was followed by direct planting of Rhizophora apiculata seedlings involving students and local communities as a form of active participation. The results showed an increase in community awareness and concern for the importance of mangrove ecosystems in preventing coastal abrasion. Cross-sectoral participation from academia, local government, and the community further strengthened the sustainability of the rehabilitation program. The planting activity also provided students with hands-on educational experience in applying scientific knowledge in practice. Furthermore, the developed mangrove area has the potential to serve as an educational ecotourism site that supports coastal community empowerment. Thus, this activity not only contributes to the sustainability of coastal ecosystems but also opens opportunities for environmentally oriented management focused on conservation and community welfare improvement.